Geographic information system approach on management prioriti-zation of Gubawan watershed, Basilan, Philippines using morpho-metric analysis (Revista de Investigaciones Universidad del Quindío, 2022)
The research study was conducted in the Gubawan watershed, Basilan province. The watershed has a total area of 19,348.48 hectares (193.48 km2). The study aims to characterize the watershed in terms of morphometric analysis and rank it according to management prioritization. Digital Elevation Model (DEM) is used and processed in GIS software to produce maps and other data. Some linear and shape morphometric parameters are used in the evaluation for ranking. The study revealed that sub-watersheds (SW5) and (SW1) ranked first and seventh. High-risk sub-watershed was given priority in terms of management prioritization to reduce soil erosion, enhanced infiltration, and promote conservation farming.
Keywords: GIS; Morphometry; Management prioritization; Gubawan watershed; Basilan; Geographic Information System